2016
DOI: 10.1108/ijem-03-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the research efficiency of higher education institutions in Chile

Abstract: Purpose – The purpose of this paper is to assess the research efficiency of the Chilean higher education institutions (HEIs). As it has been argued in the literature, universities in Chile are far from being considered research-oriented institutions. Current governmental reforms have put pressures on the efficient use of public resources, especially, public expenditures in higher education. In response, the proposed data-driven approach can be used to inform educational managers and policy make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 35 publications
2
44
0
4
Order By: Relevance
“…This ratio of Levels I/II to Levels III/IV tests contrasts sharply with results reported in other developing societies (Hallinger, 2017; Hallinger and Chen, 2015; Hallinger and Hammad, 2017), as well as the early EDLM literature in the USA (Bridges, 1982; Campbell, 1979; Campbell and Faber, 1961; Haller, 1979; Hallinger and Heck, 1996). This finding reaffirms the existence of regional expertise in advanced quantitative research (Cervini, 2009; Collado et al, 2015; Javier Murillo and Román, 2011; Martínez Abad and Chaparro Caso López, 2017; Muñoz, 2016; Muñoz et al, 2016; Shin et al, 2013; Troncoso et al, 2016; Valenzuela et al, 2016; Wilms and Somer, 2001).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…This ratio of Levels I/II to Levels III/IV tests contrasts sharply with results reported in other developing societies (Hallinger, 2017; Hallinger and Chen, 2015; Hallinger and Hammad, 2017), as well as the early EDLM literature in the USA (Bridges, 1982; Campbell, 1979; Campbell and Faber, 1961; Haller, 1979; Hallinger and Heck, 1996). This finding reaffirms the existence of regional expertise in advanced quantitative research (Cervini, 2009; Collado et al, 2015; Javier Murillo and Román, 2011; Martínez Abad and Chaparro Caso López, 2017; Muñoz, 2016; Muñoz et al, 2016; Shin et al, 2013; Troncoso et al, 2016; Valenzuela et al, 2016; Wilms and Somer, 2001).…”
Section: Resultssupporting
confidence: 59%
“…Scholars have suggested that SESI maintains a rigorous standard of review with a focus on sophisticated quantitative research that is often beyond the reach of scholars in developing societies (Hallinger, 2017). The majority of the articles published in SESI were Chilean in origin and employed sophisticated quantitative analysis (Bellei et al, 2016; Collado et al, 2015; Elaqua et al, 2011, 2016; Fromm et al, 2016; Munoz, 2016; Troncoso et al, 2016; Valenzuela et al, 2016). This pattern of journal publication strengthens the impression that significant research capacity does exist in Latin America, though it may not be broadly or evenly distributed.…”
Section: Resultsmentioning
confidence: 99%
“…4) The study was conducted in a private Chilean University, and it is necessary to replicate these findings including other types of higher education settings (e.g. technical, public or traditional universities), considering the differences between public and private institutions reported by literature (Muñoz, 2016). 5) A vast majority of the previous research, identified during our literature review, derives from doctoral studies.…”
Section: Discussionmentioning
confidence: 99%
“…Table 6 shows the detailed system and stage efficiencies of each DMU obtained from Models (4)- (14). The values in the last three rows of Table 6 are the average efficiencies and MPIs of the 18 HEIs for the three years.…”
Section: Yearly Efficiencies and Performance Interfacesmentioning
confidence: 99%